[tex](x+y-10)^{2} [/tex]+[tex](2x-y+8)^{2} [/tex]=0
Egalam fiecare paranteza cu 0 si obtinem
x+y-10=0 ⇒ x+y=10
2x-y+8=0 ⇒ 2x-y= -8 ⇔2x=y-8 ⇔ x=[tex] \frac{y-8}{2} [/tex]
Inlocuim x=[tex] \frac{y-8}{2} [/tex] in relatia x+y=10 si obtinem
[tex] \frac{y-8}{2} [/tex]+y=10 Aducem la acelasi numitor si avem y-8+2y=20
3y=28 ⇒ y=[tex] \frac{28}{3} [/tex]
X=[tex] \frac{ \frac{28}{3}-8}{2}= \frac{ \frac{28}{3}- \frac{24}{3} }{2}= \frac{ \frac{4}{3} }{2} = \frac{4}{3} * \frac{1}{2} = \frac{2}{3} [/tex]
Deci x= \frac{2}{3} si y=[tex] \frac{28}{3} [/tex]